Heavy metals in water and sediment of Way Ratai River due to small-scale gold mining activities in Pesawaran Regency, Lampung Province (Part II: zinc, copper, cadmium, iron, and manganese) - Istighfara, Vedelya; Dermiyati, Dermiyati; Rinawati, Rinawati; Prasetia, Hendra; Fasya, Muhammad Rizki Firdaus (Journal of Degraded and Mining Lands Management, 2025)
Heavy-metal contamination in river systems poses an escalating threat to aquatic ecosystems and public health. This study provides the first integrated geospatial assessment of zinc (Zn), copper (Cu), cadmium (Cd), iron (Fe), and manganese (Mn) in water and sediment of the Way Ratai River, an area increasingly impacted by artisanal gold processing. Inductively coupled plasma optical emission spectroscopy (ICP-OES) and X-ray fluorescence were used to evaluate water and sediment samples that were gathered at five key locations. Spatial interpolation via ArcGIS with an inverse distance weighting algorithm identified contamination hotspots. In river water, Zn averaged 0.05 ppm, Mn 0.009 ppm, and Fe 0.075 ppm, while Cd and Cu were below detection limits. Sediment concentrations were markedly elevated: Zn 702.62 ppm, Mn 685.60 ppm, Fe 2,954.72 ppm, and Cu 253.84 ppm. All detected metals exceeded regional background thresholds, particularly near gold-processing effluent zones, indicating significant geochemical accumulation. These findings underscore the urgent need for stringent waste-management protocols—such as coagulation and adsorption systems—to mitigate heavy-metal release and protect downstream ecosystems and human communities. This research closes a critical data gap and offers a spatially resolved framework for monitoring and remediation strategies in mining-impacted watersheds.